Quality of care of patients with acute myocardial infarction in Bulgaria: a cross-sectional study - Geraedts Max; Kalinov Krassimir; Ganova-Iolovska Milka (BMC, 2009)
Abstract Background Cardiovascular diseases are the major cause of death in Bulgaria. Because of notable differences in mortality rates between Bulgaria and other European countries, we presume a tangible difference in the management of acute myocardial infarction (AMI) and an underutilization of evidence-based treatments. In order to determine the quality of care of patients with AMI in Bulgaria, we analyzed the appropriateness of current treatments and their relation to patient characteristics. Methods We performed a descriptive cross-sectional study, using retrospectively collected data from medical charts. We included all patients with AMI, residing and admitted to hospitals in the region of Stara Zagora, Bulgaria, between September 1st and December 31st, 2004. Socioeconomic status was surveyed within the framework of a structured patient interview. We used chi-square tests with Fisher's exact probabilities to analyze the relationship between prehospital time delay age, sex, and socio-economic status of the patients and Student's independent samples t-tests to check hypotheses about means. Results From 134 patients with AMI (mean age 64.6, SD 13.2, 66% male), 7% presented to a hospital within 59 minutes, and 44% within 4 hours of symptoms onset. The use of Heparin was 98%. In the first 24 hours, ASS was administrated in 82% and β-Blockers in 73% of the cases. At discharge Aspirin, β-Blockers, Angiotensin Converting Enzyme Inhibitors or AR-Blockers and Statins were used in 85%, 79%, 66%, and 43% of cases respectively. Intravenous fibrinolysis was applied in 32% of the eligible patients with ST-segment elevation. Percutaneous coronary interventions were applied in four patients within the first month after AMI. Hospital location in relation to a patient's place of residence and manner of transportation to hospital did not influence the time delay between the onset of symptoms to the start of hospital treatment. In the study region, a relation between time delay and both age and education level was observed. Conclusion The actual quality of care of patients with AMI in Bulgaria lies far from the evidence-based recommendations. Additional research and improvements in health services are needed to reduce the burden of cardiovascular disease in Bulgaria.